Pizkunde: los «renacimientos» de la lengua vasca. - ZABALTZA, XABIER (Scripta, 2018)
In this paper the concept and the traditional chronology of the Pizkunde, the «revival» of Basque identity in the second half of the 19th century, are questioned. In fact, before the emergence of nationalism, in the Basque countries there were two different «revivals», which only occasionally crossed paths. The first, which was culturalist and expressed in Basque, mostly to the north of the Pyrenees; the second, more political and mostly in Spanish, to the south. Basque nationalism has derived much more from the latter than from the former. In addition to this, in Southern Basqueland, cultural claims are largely a consequence and not a cause of political demands.